A paradigm for building fire safety - Fangrat, Jadwiga (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The aim of this study is to describe the fire safety paradigm using the concept of T. Kuhn, its components, and its role and significance for the further development of construction science, particularly the fire safety of buildings. The components of the fire safety paradigm form a complex structure (system) that is presented graphically to illustrate the interconnections and interactions between them. This structure is built by analogy with a three-dimensional coordinate system using linguistic quantities. Currently, it is not yet possible to assign a sequence of numbers representing the coordinates of a point in the space of this system. The three axes of this system determine the major groups of paradigm elements: – fire safety; – components; – activities and inputs. For each group, the components were distinguished and then briefly described and characterized, emphasizing their mutual connections and importance for the fire safety of buildings. Some significant gaps in the systemic approach to fire safety in the EU were discussed and illustrated by the example of the Grenfell Tower fire in London. The paradigm described is universal, and its universality is based on the possession of certain common attributes characteristic of the fire safety environment and their interpretation, as well as on the manner in which fire safety entities implement them. A paradigm shift will result in the introduction of a fire toxicity criterion for the assessment of construction products, which, for unknown reasons, has so far only been implemented in relation to cables. The second necessary amendment is the addition of a requirement for the spread of fires on building facades.